DO CHARACTERISTICS OF BOARD AFFECT SUSTAINABLE FINANCE DISCLOSURE? EVIDENCE: ASEAN BANKING INDUSTRY - Cakti, Reysvana Rukmana; Aryani, Y Anni (Jurnal Akuntansi dan Keuangan Indonesia, 2023)
Sustainability is an essential aspect of previous investigations on the relationship between business practices and sustainability commitments. These investigations showed how positive changes in this context have guided the banking system toward embracing sustainable finance. Therefore, the current study aimed to investigate the effect of board characteristics on sustainable finance disclosure within ASEAN banking industry, using a panel data regression model. The results showed that only board size had a positive and significant effect on sustainable finance disclosure. Meanwhile, variables such as board gender, board education, and foreign board was reported to be insignificant. This study provided valuable insight into the empirical understanding of sustainable finance disclosure, particularly within banking industry in ASEAN countries.